2021
DOI: 10.1177/1179173x211006652
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Smoking Behavior among Physicians in Riyadh, Saudi Arabia: A Cross-Sectional Study

Abstract: Background: The prevalence of smoking has increased in recent years in Saudi Arabia. Our objectives were to determine the factors affecting smoking among physicians and to assess physicians’ quitting behavior. Methods: A cross-sectional study was carried out at 3 district hospitals in Riyadh, Saudi Arabia. It involved physicians with different levels of experience and different specialties. They were asked to complete a self-administered questionnaire adapted from validated tools. The questionnaire addressed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The study found that smoking was significantly enhanced by having a smoking family member or friend, being employed as a resident, having a medical specialty, and frequently being on call. Social stress and withdrawal symptoms were the most frequent triggers of relapse [ 24 ]. Smoking among physicians is a peculiar problem because they understand the risks and harm related to smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that smoking was significantly enhanced by having a smoking family member or friend, being employed as a resident, having a medical specialty, and frequently being on call. Social stress and withdrawal symptoms were the most frequent triggers of relapse [ 24 ]. Smoking among physicians is a peculiar problem because they understand the risks and harm related to smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Riyadh, Saudi Arabia, at 3 district hospitals, 34.8% of the physicians were smokers, and the majorities were male (70.4%) physicians. Residents were the most smokers (50%), and smoking in medical interns and registrars accounted for 22.4% and 15.3%, respectively (Al Shahrani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%